Researching the methods of optimal cutting roll printing materials - Авраменко, Валерій Павлович; Ткаченко, Володимир Пилипович; Соколенко, Юлія Романівна (Eastern-European Journal of Enterprise Technologies, 2010)
Verbal and mathematical problem definition of placing rectangular linear graphic items on cutting of materials for production of printed products were formulated. Models and methods for cutting were built, computational experiments were carried out, the finding results were analyzed.